Segments of Influenza Virus Complementary RNA Synthesized In Vitro - Plotch, Stephen J. (1978)
In the presence of Mg(2+) and a specific primer, ApG or GpG, the influenza WSN virion transcriptase synthesizes large, polyadenylic acid-containing complementary RNA (cRNA) (Plotch and Krug, J. Virol., 21:24-34, 1977). After removal of its polyadenylic acid with RNase H in the presence of polydeoxythymidylic acid, the in vitro cRNA distributed into seven discrete bands during electrophoresis in acrylamide gels containing 6 M urea. The eight known segments of virion RNA (vRNA) also distributed into seven bands under these conditions as two, rather than the expected three, large-sized segments were resolved. Each of the in vitro cRNA segments migrated slightly faster than the corresponding vRNA segment. To determine whether this difference in mobility reflects a difference in size between cRNA and vRNA, the double-stranded RNA formed by annealing labeled in vitro cRNA to unlabeled vRNA was subjected to various nuclease treatments and was analyzed by gel electrophoresis. Hybrids treated with RNase T2 or a combination of RNase T2 and RNase H migrated slightly faster than those treated only with RNase H, indicating that RNase T2 removed an RNA sequence other than polyadenylic acid, most probably a short sequence of vRNA not hydrogen bonded to cRNA. These results suggest that the in vitro cRNA segments are shorter than, and thus incomplete transcripts of the corresponding vRNA segments. All eight hybrids were resolved by gel electrophoresis, indicating that all eight vRNA segments are transcribed into cRNA in vitro. We also present evidence suggesting that the ApG primer initiates in vitro transcription exactly at the 3′ end of vRNA.